2017
DOI: 10.1186/s13568-017-0358-5
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and visual research on the microbial induced carbonate precipitation by Pseudomonas aeruginosa

Abstract: Microbial induced carbonate precipitation (MICP) is a common occurrence of geochemistry influences in many fields, such as biological, geographical, and engineering systems. However, the processes that control interactions between carbonate biomineralization and biofilm properties are poorly understood. We develop a method for real time, in situ and nondestructive imaging with confocal scanning microscopy. This method provides a possible way to observe biomineralization process and the morphology of biomineral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 44 publications
(47 reference statements)
2
27
0
Order By: Relevance
“…Bacteria are well known to mineralize calcium, and denitrification is one of the metabolic processes associated with calcium carbonate formation ( 58 ). Calcium carbonate has been detected in bacterial biofilms, for example, in the case of Pseudomonas aeruginosa ( 59 ); thus, we speculate that BapA might function to nucleate the formation of a calcium mineral that is required for cell-cell and cell-surface interactions. An alternative possibility is that binding of calcium ions to BapA alters the structure of the protein in a way that is required for it to function as an adhesin.…”
Section: Discussionmentioning
confidence: 87%
“…Bacteria are well known to mineralize calcium, and denitrification is one of the metabolic processes associated with calcium carbonate formation ( 58 ). Calcium carbonate has been detected in bacterial biofilms, for example, in the case of Pseudomonas aeruginosa ( 59 ); thus, we speculate that BapA might function to nucleate the formation of a calcium mineral that is required for cell-cell and cell-surface interactions. An alternative possibility is that binding of calcium ions to BapA alters the structure of the protein in a way that is required for it to function as an adhesin.…”
Section: Discussionmentioning
confidence: 87%
“…The removal of organic matter in the hybrid MBBR-MBR system subjected to variable salinity conditions was very good during the whole steady-state operation period with 99.51% removal of BOD 5 and 88.64% removal of COD for mean influent values of 293. 33 [20]. For the constant salinity scenario, the removal rates of BOD 5 and COD were 98.09% and 88.55% for influent concentrations of 408.33 ± 46.18 mg-BOD 5 L −1 and 654.07 ± 154.57 mg-COD L −1 , respectively.…”
Section: Physical-chemical Parameters and Nutrient Removalmentioning
confidence: 96%
“…For the constant salinity condition, the identified phylotypes with >1% relative abundance reported for calcite precipitation were Nocardioides (1.163% to 1.694%) [31], Brevibacterium (0.604% to 2.324%) [32], and Pseudomonas (0.671% to 2.284%) [33]. For the case of struvite precipitation, the identified phylotypes were Corynebacterium (0.492% to 2.374%) [34], Brevibacterium (0.604% to 2.324%) [35], and Ochrobactrum (0.671% to 2.284%) [15].…”
Section: Identification Of Bacterial Species Associated With Mineral mentioning
confidence: 98%
See 1 more Smart Citation
“…An important requirement for effective MICP process is the presence of microorganism which serves as nucleation site. The microorganisms interact with each other and solid surface to form what is known as biomass or biofilm, which is a combination of buildup of single or complex organism cells and extracellular polymeric substances (EPS) [8,39]. Proto et al [65] reported that the high specific surface area of soils facilitates the formation of biofilms that significantly have the potential to influence the engineering behavior of soil.…”
Section: Introductionmentioning
confidence: 99%